The Interaction of CDH20 With β-Catenin Inhibits Cervical Cancer Cell Migration and Invasion via TGF-β/Smad/SNAIL Mediated EMT - Li, Chao; Ao, Hongfeng; Chen, Guofang; Wang, Fang; Li, Fang (Frontiers in Oncology, 2020)
Cancer-associated cadherin 20 (CDH20) is a novel identified cadherin that is genetically altered in several types of human cancer, including cervical cancer. However, its involvement in the progression of cervical cancer remains unknown. In this study, we show that CDH20 was downregulated in clinical cervical cancer samples and its expression correlated with cervical cancer clinical features. CDH20 negatively regulated the migration and invasion of cervical cancer cells. CDH20 increased the expression and promoted the cytoplasm and membrane translocation of β-catenin, and interacted with β-catenin. Mechanistically, CDH20/β-catenin suppressed transforming growth factor-β (TGF-β)-induced epithelial-to-mesenchymal transition (EMT) by downregulating Snail through reducing the phosphorylation and nuclear translocation of Smad2/3. Taken together, our data suggest that CDH20 may act as a tumor suppressor that interacts with β-catenin to inhibit cervical cancer cell migration and invasion via TGF-β/Smad/Snail mediated EMT.